Selection of suitable reference genes for gene expression studies in HMC3 cell line by quantitative real-time RT-PCR - Martina Fazzina; Matteo Bergonzoni; Francesca Massenzio; Barbara Monti; Flavia Frabetti; Raffaella Casadei (Scientific Reports)
Abstract Microglia represent the primary immune defense system within the central nervous system and play a role in the inflammatory processes occurring in numerous disorders, such as Parkinson’s disease (PD). PD onset and progression are associated with factors considered possible causes of neuroinflammation, i.e. genetic mutations. In vitro models of microglial cells were established to identify specific molecular targets in PD through the analysis of gene expression data. Recently, the Human Microglial Clone 3 cell line (HMC3) has been characterized and a new human microglia model has emerged. Here we perform RT-qPCR analyses to evaluate the expression of ten reference genes in HMC3, untreated or stimulated to a pro-inflammatory status. The comparative ∆CT method, BestKeeper, Normfinder, geNorm and RefFinder algorithms were used to assess the stability of the candidate genes. The results showed that the most suitable internal controls are HPRT1, RPS18 and B2M genes. In addition, the most stable and unstable reference genes were used to normalize the expression of a gene of interest in HMC3, resulting in a difference in the statistical significance in cells treated with Rotenone. This is the first reference gene validation study in HMC3 cell line in pro-inflammatory status and can contribute to more reliable gene expression analysis in the field of neurodegenerative and neuroinflammatory research.